A general overview of geoconservation in Portugal - Brilha, J. B. (2005)
Geoconservation in Portugal started with some delay in relation to other European countries. The reason for this is threefold: i) the Nature Conservation legislation has been usually inappropriate for the conservation of the geological heritage; ii) the Nature Conservation Institute generally does not take into account geoheritage as part of natural heritage; and iii) only recently, the Portuguese geological community begun to realize the necessity to get involved in geoconservation.